Impact of sodium-glucose cotransporter-2 inhibitor use on peak VO2 in advanced heart failure patients - Desai, A.; Sharma, S.; Abuah, N.; Jang, J.; Desai, S.; Paghdhar, S.; Goswami, R. M. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Advanced heart failure (HF) is an epidemic that affects multiple organ systems with high morbidity and mortality rates despite optimal medical therapy (OMT) and remains the leading cause of hospitalizations in type 2 diabetes-related cardiovascular disease. The addition of sodium-glucose co-transporter inhibitors (SGLT2i) in treating these patients has seen improved mortality and hospital admission rates. As such, we felt it was important to investigate whether the use of SGLT2i improved functional capacity in patients with HF when compared to OMT by evaluating maximum oxygen consumption (peak VO2) using cardiopulmonary exercise testing (CPET). Methods We found 94 heart failure patients between August 2020 and August 2021 who underwent CPET before and after treatment at Mayo Clinic in Florida. 50 patients received OMT and 44 received OMT and SGLT2i therapy. CPET results before and after were compared for each group. Results The baseline ejection fraction was not significantly different between groups, with the OMT group at 38% and the SGLT2i group at 33%, p = 0.10. OMT patients were found to have a significantly lower hemoglobin A1c of 5.7 (5.4–6.1) compared to those with SGLT2i therapy of 6.4 (5.8–7.1), p = 0.01. The baseline peak VO2 was 17.3 ml/kg/min (13.3–21.6) in the OMT group and 17.3 ml/kg/min (14.4–18.9) in the SGLT2i group, p = 0.18, not significantly different. The interesting finding is that the follow-up peak VO2 at one year for the OMT group was 17 ml/kg/min (13.3–21.6), which was not significantly different from the SGLT2i group peak VO2 of 17 ml/kg/min (14.6–19.6), p = 0.19. Our study is the first to compare before and after peak VO2 values of the OMT+SGLT2i group to the patient's own baseline and we found no significant improvement. Conclusion Our single-center data shows no improvement in functional capacity after the addition of SGLT2i therapy to OMT in patients with advanced heart failure. Improved hospitalization and symptoms may be attributed to other numerous effects of SGLT2i such as volume management.